1991
DOI: 10.1111/j.1468-2311.1991.tb00710.x
|View full text |Cite
|
Sign up to set email alerts
|

Parole and its Problems: A Canadian‐English Comparison

Abstract: The parole system of England and Wales is contrasted with that of Canada. Recent reviews of the system have taken place in both countries. There is agreement between the reviewing bodies on the centrality of risk assessment to parole. In the Canadian case, this concern extends to the development and maintenance of statistical predictors to make the system consonant with its stated purpose. Despite the existence of an excellent statistical basis for similar developments in England, the possibilities are all but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…Our findings suggested that penal interventions, including community supervision, were relatively more effective than is commonly supposed (see Hedderman and Sugg, 1996). The slower rate of re-arrest found for offenders under community supervision accords with previous evaluations (see Polvi and Pease, 1991) -namely, that supervision at least delays recidivism and may offer a less costly context for managing and treating sex offenders. Thus custodial or community interventions were salutary in delaying, if not in preventing, the ultimate risks of re-arrest.…”
Section: Sex Offender Risk and Penal Policysupporting
confidence: 74%
“…Our findings suggested that penal interventions, including community supervision, were relatively more effective than is commonly supposed (see Hedderman and Sugg, 1996). The slower rate of re-arrest found for offenders under community supervision accords with previous evaluations (see Polvi and Pease, 1991) -namely, that supervision at least delays recidivism and may offer a less costly context for managing and treating sex offenders. Thus custodial or community interventions were salutary in delaying, if not in preventing, the ultimate risks of re-arrest.…”
Section: Sex Offender Risk and Penal Policysupporting
confidence: 74%
“…With regard to auto theft, between 6% and 49% of motor vehicle thefts were repeatedly targeted. Bennett and Durie (1999) and Polvi and Pease (1991) concluded that there were three options for locations that were repeatedly victimized in a short period of time: the same offender returns, the offender tells another offender and he returns, or the home is an attractive target for all burglars. These studies highlight the need for police and researchers to examine the location where the crime occurs and the environmental characteristics that may make it more attractive.…”
Section: Repeat and "Near Repeat" Victimizationmentioning
confidence: 99%